Efficacy and Safety of Fondaparinux Versus Enoxaparin in The Management of Unstable Angina and NSTEMI (Bangladesh Heart Journal, 2024)
Background: Unstable angina (UA) and Non-ST elevation myocardial infarction (NSTEMI) impose significant health and economic burden on Bangladesh. Anticoagulants are recommended as standard therapy by various clinical practice guidelines. Recent studies have shown fondaparinux's superiority over enoxaparin in patients with UA & NSTEMI, especially in bleeding reduction. The description of this finding has not yet been documented in any study from Bangladesh. This study aimed to evaluate the efficacy and safety of fondaparinux compared with enoxaparin in the management of UA & NSTEMI.Methods: This prospective observational study included 177 patients (fondaparinux=87, enoxaparin=90) with UA and NSTEMI admitted to the Department of Cardiology of Abdul Malek Ukil Medical College Hospital, Noakhali, Bangladesh. The primary outcome was to determine whether fondaparinux was non-inferior to enoxaparin in preventing the composite of death, new myocardial infarction, and refractory ischemia, readmission in the hospital for heart failure within six months after anticoagulant therapy. The primary safety outcome was to evaluate the rates of major bleeds in the two groups.Results: The minor (6.9% versus 20%, p=0.002) and major (0% versus 3.3%, p=0.002) bleeding events were less frequently observed with Fondaparinux than enoxaparin. Myocardial ischemia (3.4% vs. 14.4%, p=0.011) and recurrent ischemia (11.5% vs. 24.4%, p=0.025) were less frequent in Fondaparinux than in the enoxaparin group. Fondaparinux was associated with a reduced number of deaths in 3 months (6.2% vs. 12.5%) and 6 months (5.1% vs. 13.3%) without any statistical significance (p>0.05).  In the fondaparinux group, 20.7% of patients experienced a composite event within 6 months, compared with 40% of patients in the enoxaparin group (OR:0.659, 95% CI 0.500-0.867, p=0.005).Conclusion: Similarly, to recently published data in international literature, fondaparinux proved superior to enoxaparin for the Bangladeshi population, with a significant reduction of combined events and bleeding in patients with UA & NSTEMI.Bangladesh Heart Journal 2024; 39(1): 31-37